The imaginaries of the city of Norilsk, from the Soviet industrial utopia to the contemporary nickel legend - Vergnac, Camille (Vilnius University Open Series, 2024)
Norilsk is a polar city in Russia, located to the South of the Taimyr Peninsula in the Arctic Circle. The city’s surroundings are rich in unique deposits of polymetallic ores, and life in the city is organised around metal extraction. This is a reason why Norilsk is an interesting object for analysis of the social representation of the city’s image. Social representation is a fairly new socio-philosophical concept. By the word ‘representation’ we mean perceptions that are formed on the basis of reality. In the case of Norilsk, it is the result of all perceptions of the city and its environment. The study is based on contemporary documentary films, geographical, historical and journalistic documents. The analysis of perceptions of Norilsk allows us to understand the reasons for ideological debates around the history of Russia, such as discussions about memorials to victims of political repressions. Statements about Norilsk are contradictory. Negative statements are related to negative perceptions of the city, while positive statements are related to the residents’ love for their city. The analysis of representations related to the architecture of Norilsk allows us to identify gaps in the official discourse about the foundation of the city and explore its historical background. The study has revealed that the Soviet architectural heritage is well-preserved and documented, while statements about buildings associated with the Gulag are relegated to a marginalised space. Consideration of external and local representations of Norilsk allows us to understand the process of rewriting the history of the city.
Keywords: Norilsk; Gulag; architecture; imaginaries; rewriting history